Characterization of antagonistic‐potential of two Bacillus strains and their biocontrol activity against Rhizoctonia solani in tomato. (26th November 2013) - Solanki, Manoj Kumar; Singh, Rajesh Kumar; Srivastava, Supriya; Kumar, Sudheer; Kashyap, Prem Lal; Srivastava, Alok K.
<x xml:space="preserve">Abstract</x> To investigate the biocontrol mechanism of two antagonistic Bacillus strains (Bacillus subtilis MB14 and Bacillus amyloliquefaciens MB101), three in vitro antagonism assays were screened and the results were concluded that both strains inhibited Rhizoctonia solani growth in a similar manner by dual culture assay, but the maximum percent of inhibition only resulted with MB101 by volatile and diffusible metabolite assays. Moreover, cell free supernatant (CFS) of MB101 also showed significant (p > 0.05) growth inhibition as compared to MB14, when 10 and 20% CFS mix with the growth medium of R. solani. After in vitro‐validation, both strains were evaluated under greenhouse and the results concluded that strain MB101 had significant biocontrol potential as compared to MB14. Strain MB101 was enhanced the plant height, biomass and chlorophyll content of tomato plant through a higher degree of root colonization. In field trials, strain MB101 showed higher lessening in root rot symptoms with significant fruit yield as compare to strain MB14 and infected control. Next to the field study, the presence of four antibiotic genes (srfAA, fenD, ituC, and bmyB) also concluded the antifungal nature of both Bacillus strains. Phylogenetic analysis of protein sequences revealed a close relatedness of three genes (srfAA, fenD, and ituC) with earlier reported sequences of B. subtilis and B. amyloliquefaciens. However, bmyB showed heterogeneity in among both strains (MB14 and MB101) and it may be concluded that higher degree of antagonism, root colonization and different antibiotic producing genes may play an important role in biocontrol mechanism of strain MB101.